Dialogic Book-Sharing as a Privileged Intersubjective Space - Murray, Lynne; Rayson, Holly; Ferrari, Pier-Francesco; Wass, Sam V.; Cooper, Peter J. (Frontiers in Psychology, 2022)
Parental reading to young children is well-established as being positively associated with child cognitive development, particularly their language development. Research indicates that a particular, ‘intersubjective’, form of using books with children, ‘Dialogic Book-sharing’ (DBS), is especially beneficial to infants and pre-school aged children, particularly when using picture books. The work on DBS has to date paid little attention to the theoretical and empirical underpinnings of the approach. Here, we address the question of what processes taking place during DBS confer benefits to child development, and why these processes are beneficial. In a novel integration of evidence, ranging from non-human primate communication through iconic gestures and pointing, archaeological data on Pre-hominid and early human art, to experimental and naturalistic studies of infant attention, cognitive processing and language, we argue that DBS entails core characteristics that make it a privileged intersubjective space for the promotion of child cognitive and language development. This analysis, together with the findings of DBS intervention studies, provides a powerful intellectual basis for the wide-scale promotion of DBS, especially in disadvantaged populations.